Effects of Clonorchis sinensis combined with Hepatitis B virus infection on the prognosis of patients with Hepatocellular Carcinoma following Hepatectomy. - Yuan-Kuan Li; Jing-Fei Zhao; Cheng-Lei Yang; Guo-Hua Zhan; Jie Zhang; Shang-Dong Qin; Min Zhou; Min-Jun Li; Jun-Tao Huang; Feng-Yao Kong; Hai Huang; Jia-Hao Chen; et al. (Public Library of Science (PLoS), 2023)
Background This study aimed to determine the impact of co-infection of Clonorchis sinensis (CS) and hepatitis B virus (HBV) on the prognosis of patients with hepatocellular carcinoma (HCC) following hepatectomy. Methods The clinicopathological information of 946 patients with HCC following hepatectomy was retrospectively analyzed. The patients were divided into four groups depending on whether they had CS infection and/or HBV infection: double-negative group (infected with neither CS nor HBV), simple CS group (infected with only CS), simple HBV group (infected with only HBV), and double-positive group (co-infected with CS and HBV). Kaplan-Meier curves were used to evaluate the overall survival (OS) and recurrence-free survival (RFS), while log-rank tests were used to compare survival rates. Further, Cox regression was used to perform both univariate and multivariate survival analyses to identify variables linked to the prognosis of HCC. Results The median overall survival (OS) and recurrence-free survival (RFS) in the double-positive, simple CS, simple HBV, and double-negative groups were 27 months and 9 months, 20 months and 7 months, 44 months and 12 months, and 42 months and 17 months, respectively. The double-positive group's 1-year, 3-year, and 5-year OS and RFS rates were 79.2% and 46.9%, 62.6% and 28.4%, 47.8%, and 12.2%, respectively. The simple CS group's 1-year, 3-year, and 5-year OS and RFS rates were 86.3% and 41.5%, 56.5% and 27.7%, 50.2%, and 18.5%, respectively. The simple HBV group's 1-year, 3-year, and 5-year OS and RFS rates were 89.8% and 56.0%, 72.5% and 30.5%, 63.8%, and 19.9%, respectively. The double-negative group's 1-year, 3-year, and 5-year OS and RFS rates were 91.5% and 62.3%, 76.1% and 32.9%, 64.0%, and 22.4%, respectively. Further, according to a Cox multivariate analysis, tumor size (> 5cm), Edmonson grade (III-IV), BCLC-C stage, and tumor satellite focus were independent risk factors for RFS and OS in patients with HCC. Conclusion Patients with HCC and Clonorchis sinensis infection experience a poor prognosis after hepatectomy, regardless of whether they are co-infected with HBV.